The Object as a Series of Its Acts - Vesnić, Snežana; Bojanić, Petar; Ćipranić, Miloš (Filozofski vestnik, 2023)
Our intention is to construct the conditions for a new position that more closely explains the reality of the object (its location, concreteness, possibility of being seen, extension, instantaneousness, etc.), but also the object’s movement, the “situation” in which it is or becomes a potential agent that “works,” influences us and incites us to movement towards us, indeed gives us a turn towards an ideal object and its realization. Using a variety of texts that thematize the object, a few passages from Hegel, we attempt to reveal connections between key architectural (and not only architectural) concepts, form a given epistemological order, and differentiate amongst basic acts and operations that could be ascribed to the object.